1994
DOI: 10.1111/j.1464-5491.1994.tb00337.x
|View full text |Cite
|
Sign up to set email alerts
|

Random Blood Glucose Estimation in Type 2 Diabetes: Does it Reflect Overall Glycaemic Control?

Abstract: The relationship between clinic-measured random blood glucose and glycated haemoglobin was investigated in 204 non-insulin-dependent diabetic patients to determine the value of random blood glucose on management decisions in these patients. Treatment was with diet alone in 104 patients (51%: Group 1), and diet and oral hypoglycaemic agents in 100 patients (49%: Group 2). Random blood glucose and glycated haemoglobin were lower in Group 1 than Group 2 (10.9 +/- 4.0 vs 13.0 +/- 4.0 mmol l-1, p < 0.001, and 8.5 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 10 publications
4
19
0
Order By: Relevance
“…This phenomenon has been observed in several studies (26, 36,37) and may re flect the common clinical practice of placing This phenomenon has been observed in several studies (26, 36,37) and may re flect the common clinical practice of placing …”
Section: O N C L U S I O N S -mentioning
confidence: 75%
“…This phenomenon has been observed in several studies (26, 36,37) and may re flect the common clinical practice of placing This phenomenon has been observed in several studies (26, 36,37) and may re flect the common clinical practice of placing …”
Section: O N C L U S I O N S -mentioning
confidence: 75%
“…Gill et al . () and Gulliford () investigated British patients with type 2 DM and found that RBG<10.0 mmol/l had a high PPV (96%) for HbA 1c <10.0% but poor NPV (46%). An explanation for the variation in results could be that patients with type 2 DM in this study in general had a better glycaemic control than patients in the two previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Information on the diagnostic accuracy of RBG on long‐term glycaemic control is sparse, but two studies have shown that RBG had a high sensitivity or high positive predictive value (PPV) for suboptimal glycaemic control (HbA 1c : 7.8–10.0%) among patients with DM (Gill et al . ; Otieno et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Gill et al [9] suggested that clinic measured random blood glucose plasma levels below 10 mmol/L predict acceptable overall glycemic control in NIDDM patients, particularly on di et al one. A clinic measured random blood plasma glucose above 10 mmol/L was of limited value in predicting glycated hemoglobin values above 10% and a blood glucose cut off of 14 mmol/L is more useful.…”
Section: Random Plasma Glucose Testmentioning
confidence: 99%